Validating public governance quality measurement scale with application to domestic private investment in renewable energy for electricity generation - Abdulkarim, Yusuf Daiyabu; Abd Manaf, Nor Aziah; Mohamad Hsbollah, Hafizah (EconJournals, 2022)
Measurement scale plays an important role in academic research without which an instrument could not be developed. The goal of this study is to validate the measurement scale of public governance quality (PGQ) with application to renewable energy investment by means of comprehensive scale validation procedures. Data was collected from 357 individual key conventional energy stakeholders in Nigeria using survey questionnaires. Confirmatory Analysis (CFA) using SPSS version 25 and PLS-SEM version 3.8 was used to determine the reliability and validity of the measures of PGQ. The results from the study offer proof that the measurement scale of the PGQ has fulfilled the standards for reliability and validity. Practically, the validated scale introduced acts as a measurement for PGQ in the area of renewable energy domestic private investment. Also, the validated scale may be used to determine investors’ view regarding PGQ in a country or entity as to whether the level of governance is below average, average or high which consequently influence renewable energy investment. Still, it may be used to determine the effect of PGQ on investment intentions and/or behaviours when engaging with domestic investors. In due course, the measurement scale will allow policy makers across the globe to adapt energy investment decisions that will draw domestic private investment particularly in renewable energy based on researches conducted using the scale.